EFFECT OF INCOME, OPERATIONAL EXPENSES, AND INTEREST EXPENSES ON NET PROFIT: In the Company PT Citra Marga Lintas Jabar Period 2018-2021 - Nabila, Jasmine; Ridwan, Ridwan (Journal of Accounting Inaba, 2023)
This study aims to determine the effect of income, operating expenses, and interest expenses on net income. This research is quantitative research with a descriptive and verification approach. The data used is secondary data obtained from the annual financial reports of PT Citra Marga Lintas Jabar for the 2018-2021 period. By processing data using the IBM SPSS 26.0 program. The results of the study show that (1) the lowest income in February 2018 and the highest income in December 2021 (2) the lowest operating expenses in March 2019 and the highest operating expenses in September 2019 (3) the lowest interest expenses in 2018 and interest expenses the highest in 2021 (4) the lowest Net Profit in May 2018 and the highest Net Profit in March 2021 (5) Income correlation is very weak (6) Operating Expenses has weak correlation (7) Interest Expenses has very strong correlation (8) Income has a negative effect on Net Profit partially (9) Operating Expenses have a positive effect on Net Income partially (10) Interest Expenses have a positive effect on Net Profit partially (11) Income, Operating Expenses, and Interest Expenses have an effect on Net Income simultaneously, with a coefficient of determination which is very strong, while the remaining 17.19% is influenced by other factors that are ignored in this study.